Prevalence and Associated Factors of Hand Contact Dermatitis in Female Hairdresser Students in Bangkok - แซ่จัง ปิยะ; ศุภพงษ์ สุนทร (Disease Control Journal, 2012)
Hairdresser trainees study process included shampooing, coloring, curling, bleaching, and straightening. They were exposed to many chemicals causing of multiple diseases, especially contact dermatitis. The aim of this study were to determine the prevalence and associated factors of hand contact dermatitis. A cross-sectional descriptive study was conducted during March to April, 2011. Sample was 250 female hairdresser trainees in 12 government hairdressing training centers in Bangkok who studied hairdressing program for 2 months, aged >15 years. Data was collected by questionnaire, and physical examination. Participation rate was 100%. The results showed that the prevalence of hand dermatitis was 22.4%. Factors which were statistical significantly associated with hand dermatitis were age, history of atopy, family history of atopy, rubber and food allergic history, length of hair curling study > 20 hours, and soap exposure. However, underlying disease, metal allergic history, glove type, glove used, duration of glove used and hand washing frequency were not showed relation with hand dermatitis. In conclusion, this study showed that hair curling was high risk of contact dermatitis. Hairdresser trainees should always use glove, should not use rubber glove in hair curling process, and should wash hand with soap after chemical expose. Academies should educate in contact dermatitis, working process, basic treatment, and prevention to hairdresser trainees. Moreover, surveillance of hand contact dermatitis in hairdresser trainees who were aged, history of atopy, asthma, family history of atopy, rubber and food allergic history because this group was high risk of hand contact dermatitis.